An Approach to Nonurothelial Malignancies of the Urinary Bladder in Urine Cytology. (13th November 2022) - Lew, Madelyn
Abstract : Urine cytology is an economical and convenient method of triaging patients who present with urinary symptoms as well as surveying those who have previously been diagnosed with urothelial carcinoma for recurrent or persistent disease. While the vast majority of malignancies diagnosed in urine cytology are urothelial carcinomas, it is important to recognize nonurothelial elements to inform patient prognosis and raise the possibility of involvement by a urothelial carcinoma variant, nonurothelial malignancy of the bladder, or a nonbladder primary, which may alter patient management pathways. As such, becoming familiar with morphologic features of nonurothelial malignancies in urine cytology as well as their related clinical risk factors, radiologic and cystoscopic features, differential diagnostic considerations, and the utility and pitfalls of ancillary tests can facilitate optimal patient care.